Report of a Working Group on Allium: Fifth meeting, 25-27 May 1995, Skierniewice, Poland - Gass, T.; Astley, D.; Rabinowitch, H.D.; Frison, Emile A.; European Cooperative Programme for Plant Genetic Resources; International Plant Genetic Resources Institute (1995)
The 5th meeting of the Allium working group provides information on national collections, research activities and regeneration activites related to Allium genetic resources in Europe.